EFFECTIVENESS OF NON-SURGICAL PERIODONTAL THERAPY BY GINGIVAL EXPRESSION OF IL-1β AND IL-6 - Antoaneta Mlachkova; Velitchka Dosseva-Panova; Christina Popova; Maya Kicheva (Peytchinski Publishing, 2016)
Chronic periodontitis is a multifactorial disease that is characterized by attachment loss and loss of alveolar bone. Periodontal pathogens from the subgingival microbiota are suggested as a major etiological factor for the periodontitis. The host inflammatory response against bacteria and their virulence factors underlies the current understanding of the pathogenesis of chronic periodontitis. The destructive immune response was shown to be associated with an extremely increased production of inflammatory cytokines in periodontal tissues. The expression of several cytokines likeIL-1β and IL-6 is responsible for alveolar bone resorption, and loss of connective tissue attachment in chronic periodontitis. Authors reported a reduction in the levels of inflammatory cytokines after successful periodontal therapy. Measuring the levels of inflammatory factors may be diagnostic approach to assess the effectiveness of the therapy of periodontitis.